Comparative Analysis of the Chloroplast Genome for Four Pennisetum Species: Molecular Structure and Phylogenetic Relationships - Xu, Jin; Liu, Chen; Song, Yun; Li, Mingfu (Frontiers in Genetics, 2021)
The genus Pennisetum (Poaceae) is both a forage crop and staple food crop in the tropics. In this study, we obtained chloroplast genome sequences of four species of Pennisetum (P. alopecuroides, P. clandestinum, P. glaucum, and P. polystachion) using Illumina sequencing. These chloroplast genomes have circular structures of 136,346–138,119 bp, including a large single-copy region (LSC, 79,380–81,186 bp), a small single-copy region (SSC, 12,212–12,409 bp), and a pair of inverted repeat regions (IRs, 22,284–22,372 bp). The overall GC content of these chloroplast genomes was 38.6%–38.7%. The complete chloroplast genomes contained 110 different genes, including 76 protein-coding genes, 30 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. Comparative analysis of nucleotide variability identified nine intergenic spacer regions (psbA-matK, matK-rps16, trnN-trnT, trnY-trnD-psbM, petN-trnC, rbcL-psaI, petA-psbJ, psbE-petL, and rpl32-trnL), which may be used as potential DNA barcodes in future species identification and evolutionary analysis of Pennisetum. The phylogenetic analysis revealed a close relationship between P. polystachion and P. glaucum, followed by P. clandestinum and P. alopecuroides. The completed genomes of this study will help facilitate future research on the phylogenetic relationships and evolution of Pennisetum species.